Pre Participation Evaluation For Recreational Athlete: A Systematic Review - Patil, Smita Chandrakant; Anandh, S. (Journal of Neonatal Surgery, 2025)
Bckground: Pre-Participation Evaluation (PPE) is a crucial tool used to identify potential health risks before individuals engage in sports activities. While widely applied in elite athletes, its use in recreational athletes—particularly those participating in high-intensity sports—is inconsistent and under-researched. Objective: This systematic review aims to assess existing literature on PPE protocols in recreational athletes, focusing on their components, scope, effectiveness, and relevance in reducing the risk of injuries, morbidity, and sudden cardiac events. Methods: A comprehensive search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2000 and 2024. Peer-reviewed articles evaluating PPE elements, implementation, and outcomes in recreational athletes were included. The review followed PRISMA guidelines, with 32 studies selected after rigorous screening. Results: The review reveals considerable variation in PPE practices for recreational athletes. Common components include cardiovascular screening, medical history, musculoskeletal examination, and fitness assessment. However, standardized protocols are lacking, and evidence supporting the predictive value of current PPE models is limited. Some studies advocate for the inclusion of mental health and lifestyle evaluations to enhance the comprehensiveness of screening. Conclusion: Although PPE is recognized as essential, its implementation among recreational athletes remains inconsistent and lacks standardization. There is a pressing need to develop and validate structured, evidence-based PPE tools tailored to recreational participants in high-intensity sports to improve safety and encourage sustained physical activity.